Hubungan Pengungkapan Diri (Self Disclosure) dengan Tingkat Stres pada Mahasiswa Tingkat Akhir di STIKES Panakkukang Makassar - Abd. Malik; Suriyani, Suriyani; Mikawati, Mikawati; Napolion, Kens; Sia'tang, Weni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Students often experience stress stemming from academic activities. For final year students who often become stressors is in working on a thesis. When experiencing stress, students often share their problems with others to get support or solutions to relieve their feelings, which is called self-disclosure, which is a type of communication where a person openly discloses information about themselves (thoughts, feelings, and behaviors). Objective: To determine the relationship between self-disclosure and stress levels in final year students at STIKES Panakkukang Makassar. Research Method: Quantitative research with an analytical design and using the Cross Sectional Study approach using the Proportionate stratified random sampling technique with a sample of 163 respondents. The instrument used in this study is a questionnaire. Results: Students who experienced moderate stress with closed self-disclosure amounted to 125 (76.7Conclusion and suggestions: There is a relationship between self-disclosure and stress levels in final year students at STIKES Panakkukang Makassar. It is hoped that future researchers will research more subjects and collect more diverse data, so that the data obtained is more complete.